Cytokeratin 7 and 20 expression in gallbladder carcinoma - Kalekou, Harikleia; Miliaras, Dimosthenis (Polish Journal of Pathology, 2011)
Cytokeratin expression is being frequently used for the differential diagnosis of carcinomas originating from different sites. Among the various cytokeratins, the combination of cytokeratins (CKs) 7 and 20 is considered to be the most useful for this purpose. However, there are very few reports in the literature regarding CK7 and CK20 expression in gallbladder carcinoma (GBC). In this paper we studied the immunohistochemical expression of CK7 and CK20 in 42 GBC cases. In addition, we studied 25 randomly selected cases of lithiasis associated chronic cholecystitis (LaCC) as controls. CK7/CK20 immunoprofile was assessed in relation to tumour differentiation, depth of invasion, and p53 protein expression. Twenty-nine GBC cases (69.05%) were CK7-positive, and 12 cases (28.57%) were CK20-positive. Tumour differentiation was not correlated with CK7 or CK20 immunoreaction. Regarding tumour depth of invasion, the CK7+/CK20– group presented a significant correlation with early stage (T1) disease (p = 0.04). p53 expression was correlated with both CK7 (p = 0.05) and CK20 (p = 0.023) expression. All the cases of LaCC demonstrated diffuse intense CK7 positivity of the mucosal epithelium, while CK20 was only focally positive in 13/25 cases. Our results along with the data from the literature indicate that CK7/CK20 expression may be of clinical significance, and further investigation in this direction is needed.